2004
DOI: 10.2148/benv.30.2.138.54313
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of the Poor in Two European Metropolises: Car Dependence Versus Locality Dependence

Abstract: International audienceBased on a comparative study of the mobility of the poor in and around Paris and London, and backed by statistics and qualitative surveys, this paper exposes the greater car dependency of the poor in the UK than in France. Aside from the sociological factors (family mutual support networks), differing urban planning and transport policies are part of the reason why

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…), these residents are generally less mobile than elsewhere. They notably travel significantly less in cars (the motorisation rate is still relatively lower in these neighbourhoods), rarely use public transportation and walk more (Harzo and Rosales-Montano, 1995;Coutard et al, 2004;Mignot and Rosales-Montano, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…), these residents are generally less mobile than elsewhere. They notably travel significantly less in cars (the motorisation rate is still relatively lower in these neighbourhoods), rarely use public transportation and walk more (Harzo and Rosales-Montano, 1995;Coutard et al, 2004;Mignot and Rosales-Montano, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in terms of access to employment opportunities, as we noted in an earlier section, various indicators point to the emergence of localized micro‐labor markets. Thus, while lower levels of mobility among the poor have been categorized by various actors as indicative of ‘insularity’ or ‘confinement to a localized territory’ (Le Breton, 2005: 87), ‘withdrawal’ (Donzelot, 2004: 19), or even ‘disastrous immobility’ (Lévy, 2000: 161), we see them more as evidence of strategies that make the most effective use possible of local resources than as a form of enforced confinement within a given neighbourhood, as shown by our previous work on the French and British cases (Coutard et al. , 2002; 2004).…”
Section: Paradoxical Programsmentioning
confidence: 66%
“…Indeed, our previous work (Coutard et al. , 2002; 2004) and other studies have shown that the cost of owning and using a car is prohibitive for a significant share of households confronted with barriers to mobility, in particular low‐income households (STPP, 2003), which are often further penalized by the fluctuating and unpredictable nature of their income.…”
Section: Paradoxical Programsmentioning
confidence: 99%
See 2 more Smart Citations